Salt transport in a large agro-urban river basin: Modeling, controlling factors, and management strategies - Hocking, Craig; Bailey, Ryan T. (Frontiers in Water, 2022)
Salinity poses a severe threat to urban and agricultural areas. Excess salt can accumulate in soils and groundwater, thereby impacting crop growth and productivity. In this study we quantify the influence of driving forces on salt transport in Colorado’s South Platte River (drainage area of 62,937 km2) and investigate possible mediation strategies to reduce salinity levels in both urban and agricultural river reaches. A river salt transport model was developed that utilizes a water allocation model and accounts for multiple inputs and outputs of salt within the river network, including tributaries, wastewater treatment plants, road salt, return flows from rainfall and irrigation, and groundwater discharge. The flow and salt models are run on a monthly basis between 2002 and 2006 and tested against stream discharge and in-stream salinity concentration at multiple gage sites. A sensitivity analysis was implemented to determine the controlling factors behind salt transport in the river system by river reach and by season (spring, summer, fall, winter). SA results were used to guide selection of management practices (n = 256) that can control salinity in both urban and agricultural areas. For urban areas, during spring/summer and fall/winter, the most efficient management practice is to decrease WWTP effluent salinity concentration by 35% and to decrease applied road salt by 35%, respectively, resulting in decreases of 10-30% decrease in river salt concentration. For agricultural areas, the only management practices that achieve an in-river salinity concentration (1,000 mg/L) that prevents crop yield decrease during irrigation are aggressive practices that focus on WWTP effluent concentration, return flow salinity, and urban road salt. Results points to the extreme challenge of managing salinity in the South Platte River Basin and other similar basins and the aggressive urban approaches that must be implemented to sustain irrigation practices in the downstream regions of the basin.